LixFePO4 -ийн фазын салалтын кинетик болон соронзон шинж чанарын судалгаа - Н., Төвжаргал; Б. Бат-Oтгон; Ж., Даваасамбуу; Г., Еколд (Scientific transaction of the National University of Mongolia. Physics, 2022)
Time-resolved X-ray diffraction was used to investigate the kinetics of phase separation in polycrystalline LixFePO4 samples which were quenched from the homogeneous phase to lower temperatures. On quenching from 380°C (homogeneous phase) to ageing various temperatures, we observed that the structural features of the formation of the two product phases LiFePO4 and orthorhombic FePO4, i.e. the splitting of selected Bragg reflections, appear on a time-scale of hours. The kinetic behaviour seems to vary strongly with the ageing temperatures. In the case of quenching to temperatures lower than 50°C, no significant splitting of Bragg reflections is observed. Hence, the homogeneous phase may be stabilised by quenching to sufficiently low temperatures. We have studied the magnetic properties of the samples by SQUID-magnetometry. The partially delithiated samples show the known temperature dependence of the magnetic susceptibility with ordering temperatures of about 122K (FePO4) and 50K (LiFePO4). In order to create a single phase, the samples were quenched from the homogeneous phase to room temperature. Obviously, Néel temperatures of these samples were observed in between the values of pure compounds and depend on the overall composition.